Comprehensive Diagnostic Anatomy of Normal and Osteoarthritic Canine Stifle Joint - Gupta, N.; Vaish, R.; Shahi, A.; Gupta, D. K.; Mishra, A.; Jain, P.; Dubey, A.; Tekam, S. (International Journal of Bio-resource and Stress Management, 2025)
The experiment was conducted from October 2021 to August 2023 at the Veterinary College, Jabalpur, to study the stifle joint of dogs, to investigate morphological alterations in osteoarthritic stifle joints using radiography, computed tomography (CT), and ultrasonography, and to compare them with those of healthy stifle joints. In addition to these, gross observations of the stifle joint are recorded in the carcasses of dogs to set baseline data. Osteoarthritis is a disease characterized by an imbalance between the synthesis and degeneration of articular cartilage components. The stifle joint is a complex synovial joint prone to osteoarthritis. Present work was conducted on the stifle joint of 24 dogs, divided into three groups: group I and II, which included carcasses of 06 young (3-5 months) and 06 adult (more than one year) indigenous non- lame dogs, respectively, as control and group III comprised of 12 clinical cases of stifle osteoarthritis. In group II, the cranial cruciate ligament consisted of distinct craniomedial and caudolateral bundles, whereas in group I, no clear separation was seen grossly. Radiographic and CT observations showed the presence of a growth plate as a radiolucent gap between the epiphysis and metaphysis in group I dogs, while increased subchondral bone opacity at the tibial epiphysis, with osteophytes and uneven condylar margins, was visible in group III. The results of this study will be useful in the customized treatment of stifle osteoarthritis.